2006
DOI: 10.1016/j.bbrc.2006.04.081
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin species variation, HAMLET formation, and tumor cell death

Abstract: HAMLET (human α-lactalbumin made lethal to tumor cells) is a tumoricidal complex of apo α-lactalbumin and oleic acid, formed in casein after low pH treatment of human milk. This study examined if HAMLET-like complexes are present in casein from different species and if isolated α-lactalbumin from those species can form such complexes with oleic acid. Casein from human, bovine, equine and porcine milk were separated by ion exchange chromatography and active complexes were only found in human casein. This was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 37 publications
(57 reference statements)
3
80
0
Order By: Relevance
“…Whereas the purified bovine α-lactalbumin alone failed to induce any cytotoxicity, the BAMLET complex exhibited cytotoxic activity similar to that of HAMLET in L1210 mouse lymphoma cells as reported earlier (19), and in seven additional cancer cell lines tested with LC 50 values ranging from 0.05 to 0.34 mg/mL (Table 1 and Fig. 1).…”
Section: Bamlet Induces Caspase-independent Apoptosislike Cell Death supporting
confidence: 80%
See 2 more Smart Citations
“…Whereas the purified bovine α-lactalbumin alone failed to induce any cytotoxicity, the BAMLET complex exhibited cytotoxic activity similar to that of HAMLET in L1210 mouse lymphoma cells as reported earlier (19), and in seven additional cancer cell lines tested with LC 50 values ranging from 0.05 to 0.34 mg/mL (Table 1 and Fig. 1).…”
Section: Bamlet Induces Caspase-independent Apoptosislike Cell Death supporting
confidence: 80%
“…Amino-acid sequences of human, bovine, equine, caprine, and porcine show 71% homology and 63% identity with the highest sequence conservation surrounding the high affinity Ca ++ -binding site (19). Accordingly, ion exchange chromatography on oleic acid-conditioned matrixes allows the formation of protein:lipid complexes of nonhuman α-lactalbumins with yields comparable with HAMLET (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to human and bovine -LA, equine, caprine, and porcine -LA can also form cytotoxic complexes with OA [7]. Later investigations showed that the loss of tertiary structure in -LA denatured by heat-treatment or a recombinant variant of -LA in which all four cysteines have been exchanged with alanine did not prevent it from forming cytotoxic complexes using an OA conditioned column [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lactoferrin and its peptides, for example, lactoferricin [212][213][214], both possess anticancer activity by inducing apoptosis; inhibit angiogenesis, modulating the carcinogen metabolizing enzymes, and so on. Casein and casein derived peptides have antimutagenic properties, and other whey protein components, such as -lactoglobulin, -lactalbumin and serum albumin, have also demonstrated anticancer potential [212,[215][216][217]. Moreover, a recombinant adenovirus containing the human lactoferrin cDNA has been constructed and its effects against tumor growth have been investigated in mice bearing EMT6 breast cancer.…”
Section: Commercial Potential Of Milk Derived Proteins and Peptidesmentioning
confidence: 99%